2015
DOI: 10.1002/adfm.201502441
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Interesting Evidence for Template‐Induced Ferroelectric Behavior in Ultra‐Thin Titanium Dioxide Films Grown on (110) Neodymium Gallium Oxide Substrates”

Abstract: Very recently there was a report of the discovery using piezoelectric force microscopy (PFM) of a switchable ferroelectric polarization in 1.6 % tensile strained TiO 2 thin film with anatase crystal structure (see N. Deepak et al. Adv. Funct. Mater. 2014, 24, 2844. The polarization disappeared only above 450 K, which was assigned as a Curie temperature, T C . Here we have performed X-ray diffraction, second-harmonic generation (SHG) and infrared investigations of the same films. Phonon frequencies exhibit less… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…[32] However, some non-ferroelectric contributions, such as charge injection, can also result in long-lived "switched" states with relaxation time up to days. [33,34] To rule out the contributions from charge injection, electrostatic force microscopy (EFM) was performed on the electrically-written region (Figures 5g and h).…”
Section: Ferroelectric Propertiesmentioning
confidence: 99%
“…[32] However, some non-ferroelectric contributions, such as charge injection, can also result in long-lived "switched" states with relaxation time up to days. [33,34] To rule out the contributions from charge injection, electrostatic force microscopy (EFM) was performed on the electrically-written region (Figures 5g and h).…”
Section: Ferroelectric Propertiesmentioning
confidence: 99%
“…It has been reported that the materials with a polar structure have versatile properties involving pyroelectricity, ferroelectricity, and nonlinear optical behavior. 21 By combination with atomic force microscopy (AFM), Kelvin probe force micros-copy (KPFM) can enable nanometer-scale imaging of the surface potential on a wide range of polar structured materials. 22 Due to the influence of the polar structure, the separation of charge carriers can help to reduce the recombination of e−h pairs.…”
Section: Introductionmentioning
confidence: 99%
“…335 However, charge injection can result in longlived states with relaxation times that are extremely long (e.g. hours or even days, and even persisting at high temperature 344,345 ), and therefore, these also cannot be used as unambiguous proof of ferroelectric switching.…”
Section: Via Means To Distinguish Piezoelectric From Non-piezoelectmentioning
confidence: 99%